"The Miracle Mothers and Marvelous Babies": Psychosocial aspects of surrogacy - A narrative review - Ansha Patel; Pratap Kumar; P S. V. N. Sharma (Wolters Kluwer Medknow Publications, 2020)
Surrogates are described in literature as true angels "who make dreams happen." On the other hand, surrogacy has also been surrounded by several psychosocial controversies. In this review, we have made an attempt to encapsulate this topic from the multiple perspectives of individuals who are involved in the surrogacy cycle. We present to the readers the various outlooks and dilemmas of the clinicians, patient parties contracting for surrogacy, the child born out of surrogacy, and the intricate role of the mental health professionals in surrogacy arrangements. The review also throws light upon the psychosocial issues in connection to the evolving Surrogacy practices in Indian and in the Western world.